Government Spending and Central-Local Relations in Thailand's Health Sector - Lindelow, Magnus (World Bank, Washington, DC, 2013)
This paper focuses on efficiency and equity in the financing of health services, and the evolving role of central and local government in the health sector. Thailand has seen significant improvements in health outcomes and succeeded in expanding the coverage of health protection schemes over the last decades. While the achievements of Thailand's health system are undeniable, this paper highlights three key challenges: (i) inequalities in utilization and spending under different health financing schemes and across geographic areas; (ii) mounting cost pressures; and (iii) fragmentation of financing and unresolved issues concerning the respective roles of central and local governments. This paper shows that although some of the differences in utilization and spending across schemes can be explained by the age profile of members, significant variations remain even after controlling for differences. It documents large variation in resources and spending across regions, both for the system as a whole and within the respective health financing schemes. In addition, the paper highlights pressures to increase government health spending that are primarily the result of rising spending in the Universal Coverage (UC) and Civil Servant Medical Benefit Scheme (CSMBS) schemes. Cost pressures are likely to persist due to rising incidence of chronic disease, population aging, continuing pressure from health workers for greater compensation, demands for expanded benefits under the respective schemes, and the rising expectations of patients. Finally, the paper argues for a more systematic and decisive approach to decentralization of prevention and promotion functions, based on more detailed specification of the roles and responsibilities of central and local government. It also suggests that the current approach to primary care decentralization through voluntary transfer of health centers has limited potential, and that there is a need to consider local management of networks of providers that combine both general hospital and primary care services.